Decreased CD1a + and CD83 + cells in tonsillar squamous cell carcinoma regardless of HPV status - Ana Guadalupe Gama-Cuellar; Ana Lúcia Noronha Francisco; João Figueira Scarini; Fernanda Viviane Mariano; Luiz Paulo Kowalski; Rogério Gondak (University of São Paulo, 2022)
Abstract Dendritic cells (DCs) are specialized antigen-presenting cells that play a critical role in the immune response against human papillomavirus (HPV) infection, and represent a therapeutic target in cancer. Objective: To identify and quantify DCs in tonsillar squamous cell carcinoma (TSCC) under the influence of HPV infection. Methodology: CD1a and CD83 antibodies were used to identify immature dendritic cells and mature dendritic cells by immunohistochemistry in 33 primary TSCC and 10 normal tonsils (NTs), respectively. For the TSCC samples, the number of DCs per area was evaluated in the intra- and peritumoral compartments. For the NTs, the quantification of DCs was evaluated in the intra- and peritonsillar compartments. HPV detection methods were determined according to the ASCO Clinical Practice Guidelines from the College of American Pathologists Guideline (2018). Results: There were fewer intratumoral CD1a+ DCs in the HPV-positive and HPV-negative TSCC groups than in the NT group (p<0.05). In the peritumoral compartment, there were fewer CD83+ DCs in the HPV-positive and HPV-negative TSCC groups than in the NT group (p<0.001). The quantification of DCs subtypes showed no statistical differences between HPV-positive and HPV-negative TSCC groups (p>0.137). Patients with HPV-positive TSCC had significantly better overall survival rate than those with HPV-negative TSCC (p=0.004). Conclusion: Tumor activity contributes to DC depletion regardless of intralesional HPV positivity. An improved prognosis has been reported in patients with HPV-positive TSCC.